2015
DOI: 10.2298/apt1546259z
|View full text |Cite
|
Sign up to set email alerts
|

Basil (Ocimum basilicum L.) essential oil and extracts obtained by supercritical fluid extraction

Abstract: The extracts obtained from sweet basil (Ocimum basilicum L.) by hydrodistillation and supercritical fluid extraction (SFE) were qualitative and quantitative analyzed by GC-MS and GC-FID. Essential oil (EO) content of basil sample, determined by an official method, was 0.565% (V/w). The yields of basil obtained by SFE were from 0.719 to 1.483% (w/w), depending on the supercritical fluid (carbon dioxide) density (from 0.378 to 0.929 g mL-1). The dominant compounds detected in all investigated samples (EO obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Generally, S. montana EOs were characterized by high percentage of the monoterpene phenols, carvacrol and/or thymol, two isomeric compounds with different position of hydroxyl group on their phenol ring, with very close biosynthetic relationship with their precursors (γ-terpinene and p-cymene). Essential oil of O.basilicum, with linalool as the major compound, clearly indicates that the plant belongs to chemotype A (European chemotype) [32].…”
Section: Essential Oil Characterizationmentioning
confidence: 99%
“…Generally, S. montana EOs were characterized by high percentage of the monoterpene phenols, carvacrol and/or thymol, two isomeric compounds with different position of hydroxyl group on their phenol ring, with very close biosynthetic relationship with their precursors (γ-terpinene and p-cymene). Essential oil of O.basilicum, with linalool as the major compound, clearly indicates that the plant belongs to chemotype A (European chemotype) [32].…”
Section: Essential Oil Characterizationmentioning
confidence: 99%
“…These results are in agreement with Dadkhah (2010) and Jelali et al (2010) on geranium, who indicated that the essential oil percentage was increased under height value of saline condition. On the same trend, Abdalla et al (2013) and Zoran et al (2015) reported that foliar application (moringa extract) increased the percentage of essential oil and oil yield under saline irrigation water. Essential Oil yield per Hectare: Data in Table (4) presented that essential oil yield per hectare.…”
Section: Essential Oil Productionmentioning
confidence: 68%
“…Different essential oils obtained from the same plant material support the hypothesis that the composition of essential oils may vary depending on the methods of extraction used. In addition, the basil EO obtained by supercritical fluid extraction contained a lower percentage of linalool (10.14%-16.60%), but also an increased content of eugenol and δ-cadinene, compared to EO obtained by HD [47].…”
Section: Resultsmentioning
confidence: 90%